Marine Sediments Hold an Untapped Potential for Novel Taxonomic and Bioactive Bacterial Diversity - Pernille Kjersgaard Bech (American Society for Microbiology, 2020)
ABSTRACT Novel natural products have traditionally been sourced from culturable soil microorganisms, whereas marine sources have been less explored. The purpose of this study was to profile the microbial biosynthetic potential in coastal surface seawater and sandy sediment samples and to evaluate the feasibility of capturing this potential using traditional culturing methods. Amplicon sequencing of conserved ketosynthase (KS) and adenylation (AD) domains within polyketide synthase (PKS) and nonribosomal peptide synthetase (NRPS) genes showed that seawater and, in particular, sandy sediment had a high biosynthetic potential with 6,065 and 11,072 KS operational biosynthetic units (OBUs) and 3,292 and 5,691 AD OBUs, respectively, compared to that of four soil samples collected by Charlop-Powers et al. (Z. Charlop-Powers, C. C. Pregitzer, C. Lemetre, M. A. Ternei, et al., Proc Natl Acad Sci U S A 113:14811–14816, 2016, https://doi.org/10.1073/pnas.1615581113) with 7,067 KS and 1,629 AD OBUs. All three niches harbored unique OBUs (P = 0.001 for KS and P = 0.002 for AD by permutational multivariate analysis of variance [PERMANOVA]). The total colonial growth captured 1.9% of KS and 13.6% of AD OBUs from seawater and 2.2% KS and 12.5% AD OBUs from sediment. In a subset of bioactive isolates, only four KS OBUs and one AD OBU were recovered from whole-genome sequencing (WGS) of seven seawater-derived strains and one AD OBU from a sediment-derived strain, adding up to 0.028% of the original OBU diversity. Using a pairwise regression model of classified amplicon sequence variants (ASVs) to the species level, and OBUs, we suggest a method to estimate possible links between taxonomy and biosynthetic potential, which indicated that low abundance organisms may hold a disproportional share of the biosynthetic potential. Thus, marine microorganisms are a rich source of novel bioactive potential, which is difficult to access with traditional culturing methods. IMPORTANCE Since bacterial resistance to antibiotics is developing worldwide, new antibiotics are needed. Most antibiotics discovered so far have been found in soil-dwelling bacteria, so we instead targeted marine environments as a novel source of bioactive potential. We used amplicon sequencing of bioactive gene clusters in the microbiome of coastal seawater and sandy sediments and found the bioactive potential to be comparable to, but distinct from, the bioactive potential of selected soil microbiomes. Moreover, most of this potential is not captured by culturing. Comparing the biosynthetic potential to the corresponding microbiome composition suggested that minor constituents of the microbiome likely hold a disproportionally large fraction of the biosynthesis potential.